2016
DOI: 10.1021/acs.jpcc.6b05575
|View full text |Cite
|
Sign up to set email alerts
|

Low Valence Cation Doping of Bulk Cr2O3: Charge Compensation and Oxygen Vacancy Formation

Abstract: ABSTRACT:The different oxidation states of chromium allow its bulk oxide form to be reducible, facilitating the oxygen vacancy formation process, which is a key property in applications such as catalysis. Similar to other useful oxides such as TiO 2 , and CeO 2 , the effect of substitutional metal dopants in bulk Cr 2 O 3 and its effect on the electronic structure and oxygen vacancy formation are of interest, particularly in enhancing the latter. In this paper, density functional theory (DFT) calculations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 83 publications
(181 reference statements)
2
33
0
Order By: Relevance
“…Under such conditions, Cr i defects have lower formation energy compared to V Cr and both Cr i and V O have formation energies approximately equal to 1.5 eV, making Cr i and V O the dominant defects. Similarly, bulk Cr 2 O 3 samples can be strongly p-type doped with E F close to VBM, when divalent ions such as Mg are present as impurities [40]. Under such conditions, our calculations suggest that Cr i could be the dominant defect in bulk Cr 2 We have studied the diffusion of Cr and O interstitials in charge states ranging from [0, 3] and [-2, 0], respectively.…”
Section: Interstitialsmentioning
confidence: 93%
See 1 more Smart Citation
“…Under such conditions, Cr i defects have lower formation energy compared to V Cr and both Cr i and V O have formation energies approximately equal to 1.5 eV, making Cr i and V O the dominant defects. Similarly, bulk Cr 2 O 3 samples can be strongly p-type doped with E F close to VBM, when divalent ions such as Mg are present as impurities [40]. Under such conditions, our calculations suggest that Cr i could be the dominant defect in bulk Cr 2 We have studied the diffusion of Cr and O interstitials in charge states ranging from [0, 3] and [-2, 0], respectively.…”
Section: Interstitialsmentioning
confidence: 93%
“…It is noteworthy, that Cr 2 O 3 passivation films on Ni alloy substrate could be p-type doped due to trace amounts of Ni substitution [40]. For Ni doping, Fermi level in Cr 2 O 3 stabilizes at 0.4 eV above VBM [40]. Under such conditions, Cr i defects have lower formation energy compared to V Cr and both Cr i and V O have formation energies approximately equal to 1.5 eV, making Cr i and V O the dominant defects.…”
Section: Interstitialsmentioning
confidence: 99%
“…A Monkhorst-Pack (2×1×1) k-point sampling grid is used. For consistency with previous work we apply the DFT+U approach [58] to describe the Ti 3d and Cr 3d states, with U = 4.5 eV for the Ti 3d states and 3.5 eV for the Cr 3d states [59,60]. Convergence criteria for electronic and ionic relaxations are 0.0001 eV and 0.02 eV/ Å.…”
Section: Methodsmentioning
confidence: 98%
“…In addition, in previous studies, we found that this correction is necessary to describe O 2p states that result after valence band hole formation. 30,31,69 Finally, the partially filled 3d states in Cr also require a DFT + U correction to be consistently described, and here, we use U (Cr 3d) = 3.5 eV, 60 consistent with values used in other studies.…”
Section: Calculation Methodsmentioning
confidence: 99%